Prevalence and Residual Risk of HIV in Volunteer Blood Donors of Zhejiang Province, China, from 2018 to 2022 - Hong Zhu; Wei Ding; Wenjuan Han; Xiaofan Zheng; Yiqing Hu; Jie Dong; Yaling Wu; Danxiao Wu; Jinhui Liu; Faming Zhu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Blood safety levels have been significantly improved since the implementation of nucleic acid amplification technology (NAT) testing for blood donors. However, there remains a residual risk of transfusion transmission infections. This study aimed to evaluate the prevalence of HIV and its residual risk transmission among volunteer blood donors of Zhejiang Province, China, for five years after NAT implementation. Materials and Methods. All specimens and information were collected from voluntary unpaid donors at all blood services in Zhejiang Province, China, from January 2018 to December 2022. The HIV antibody or antigen and HIV RNA were detected using enzyme-linked immunosorbent assay and NAT, respectively. The HIV residual risk transmission was calculated using the incidence or window period model. Results. A total of 3,375,678 voluntary blood donors were detected, revealing an HIV prevalence of 9.92/100000. The HIV prevalence of blood donors in 12 blood services in Zhejiang Province was 6.11, 6.98, 7.45, 8.21, 8.36, 8.94, 9.04, 9.66, 9.73, 10.22, 11.80, and 12.47 per 100000 donors, without statistically significant difference observed among the services (p>0.05). The HIV prevalence of males (15.49/100000) was significantly higher compared to females (1.95/100000; p<0.05). There was an insignificant difference in HIV prevalence among blood donors of all different age groups (p>0.05), but the HIV prevalence in the 26–35 age group and 18–25 age group was significantly higher compared to the 36–45 age group (p<0.05). The difference in HIV prevalence between first-time blood donors (13.65/100,000) and repeat blood donors (6.78/100,000) was statistically significant (p<0.05). From 2018 to 2022, the HIV residual risk in blood transfusion transmission was 0.266/100000. Conclusion. The prevalence of HIV among blood donors in Zhejiang Province, China, is associated with age, gender, and times of blood donation. The HIV residual risk in blood transfusion transmission remains low in the province, and increasing the rate of repeat blood donors is beneficial to improve blood safety.